Differential expression of the ccn3 (nov) proto-oncogene in human prostate cell lines and tissues. Issue 4 (1st August 2001) - Maillard, M; Cadot, B; Ball, R Y; Sethia, K; Edwards, D R; Perbal, B; Tatoud, R
Abstract : Aims —To investigate the expression of the human ccn3 (hccn3; nov) proto-oncogene, a member of the CCN family of proteins, in prostate epithelial cells and prostate tissue samples. Methods —Normal adult prostate luminal epithelial cells immortalised by SV40 large T (PNT1A and PNT1B), metastatic tumours (LNCaP, DU-145, and PC-3), and prostate tissue samples from patients with benign prostatic hyperplasia (BPH) and prostatic adenocarcinoma were used. hccn3 (nov) mRNA was measured by the reverse transcription polymerase chain reaction (RT-PCR) and hCCN3 (NOV) protein expression was determined by immunochemistry. Results —hccn3 (nov) RNA values were higher in PC-3 cells than in the other prostate cell lines. The immortalised normal cell lines either did not express hccn3 (nov) RNA (PNT1B) or expressed very low amounts (PNT1A). BPH samples expressed variable amounts of hccn3 (nov) RNA. With the use of immunocytochemistry, all cell lines except PNT1A and PNT1B were shown to contain hCCN3 (NOV) protein. hCCN3 (NOV) was localised mainly in the epithelial compartment of BPH and adenocarcinoma samples, and there was evidence of luminal secretion. Conclusion —The overexpression of hccn3 (nov) RNA in cancer cell lines compared with other cell lines and its epithelial localisation in human prostate samples are consistent with a role for hCCN3 (NOV) in prostatic tumorigenesis.